Size dependence of electronic property in CVD-grown single-crystal graphene. (4th July 2018) - Zhu, Wen; Shi, Haohao; Gan, Wei; Li, Pengju; Wu, Chuanqiang; Chen, Shuangming; Habib, Muhammad; Liu, Hengjie; Qin, Shengyong; Song, Li
Abstract: The electronic performance of graphene is largely related to its morphology, surface, size and various synthesis conditions, mainly because of the presence of grain boundary. Better understanding on the relationship between the size and electronic property is very important for graphene's applications in potential electronics. Herein, we selectively synthesized single-crystal graphene using a chemical vapor deposition (CVD) method. The obtained CVD-graphene exhibited various sizes, ranging from 20 μ m to 120 μ m. Our measurements of field effect transistor devices revealed that the charge carrier mobility of CVD-graphene could increase from 17.8 to 720 cm 2 V −1 s −1 with the size decreasing. The better electronic performance in comparable smaller-size graphene was ascribed to less grain boundary compared with the bigger one, which was further confirmed by our observations from scanning tunneling microscope/spectroscopy (STM/STS).